2021
DOI: 10.3390/ijerph18189729
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution and Respiratory Health in Sub-Saharan African Children: A Cross-Sectional Analysis

Abstract: Ambient air pollution is projected to become a major environmental risk in sub-Saharan Africa (SSA). Research into its health impacts is hindered by limited data. We aimed to investigate the cross-sectional relationship between particulate matter with a diameter ≤ 2.5 μm (PM2.5) and prevalence of cough or acute lower respiratory infection (ALRI) among children under five in SSA. Data were collected from 31 Demographic and Health Surveys (DHS) in 21 SSA countries between 2005–2018. Prior-month average PM2.5 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Two studies conducted in Mozambique found temperature declines (2.4°C to 3.0°C or 36.32°F to 37.4°F) were associated with incidence of stroke hospitalisations [ 61 , 62 ]. In another study conducted in 21 countries of SSA, Cai et al (2021) [ 63 ] found prior month average air pollution (PM 2.5 ) exposure was not associated with cough and acute lower respiratory infections among children under five years of age. This null association may be due to several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies conducted in Mozambique found temperature declines (2.4°C to 3.0°C or 36.32°F to 37.4°F) were associated with incidence of stroke hospitalisations [ 61 , 62 ]. In another study conducted in 21 countries of SSA, Cai et al (2021) [ 63 ] found prior month average air pollution (PM 2.5 ) exposure was not associated with cough and acute lower respiratory infections among children under five years of age. This null association may be due to several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The highest range for PM 2.5 (120-973 μg/m 3 ) was reported in one study conducted in Ethiopia [ 46 ]. PM 2.5 is a common pollutant and is linked with respiratory symptoms, cancer, and cardiovascular diseases [ 9 , 63 , 65 , 66 ]. Air pollution is reported as a major cause of NCD mortality in SSA and was responsible for 1.1 million deaths across the region in 2019 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of exposure necessary for the development for ARI phenotypes may explain our findings that significant associations between PM levels and ARI symptoms are only present after a minimum of 4 months of exposure, possibly indicative that a cumulative threshold of exposure is necessary for symptoms to manifest. In a recent analysis of the association between ambient air pollution and respiratory health using satellite data and DHS surveys from 31 countries, no association between short-term PM exposure and respiratory health was found [ 92 ]. The authors used prior-month averages and evaluated two outcomes: the presence of a cough, and acute lower respiratory infection (ALRI), defined as the presence of both a cough and wheezing [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis of the association between ambient air pollution and respiratory health using satellite data and DHS surveys from 31 countries, no association between short-term PM exposure and respiratory health was found [ 92 ]. The authors used prior-month averages and evaluated two outcomes: the presence of a cough, and acute lower respiratory infection (ALRI), defined as the presence of both a cough and wheezing [ 92 ]. The lack of short-term associations, similar to our findings, reinforces the need for both more accurate ambient pollution measures as an exposure and better pathophysiological characterization of the outcome variables.…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory infections were once a major health problem in Indonesia 7 . This disease can usually occur as a result of viruses, bacteria, or particles that can enter the lungs causing serious infections 8 . ARI that occurs in children, if not treated with proper treatment can cause death 9 .…”
Section: Introductionmentioning
confidence: 99%